Sports Coverage on BBC ALBA: Content, Value, and Position in the Scottish Broadcasting Landscape. (April 2019) - Ramon, Xavier; Haynes, Richard
Through a mixed-method approach, we examine the sports programming offered by BBC ALBA between 2008 and 2016 and identify the value that the channel creates in Scotland through its diverse sports portfolio. In an increasingly cluttered and complex scenario where pay-TV giants Sky and BT hold a plethora of top-tier rights and BBC Scotland and STV cannot fit more sport into their schedules, BBC ALBA serves Gaelic-speaking and national audiences with a regular diet of quality sports programming. Beyond being instrumental to filling schedules, sports content has been a gateway for Gaelic, a key driver of BBC ALBA's investment in the creative sector and a contributor to the development of grassroots sport in Scotland. However, the financial situation under which the channel operates makes it very difficult to sustain and improve its current position. This case study demonstrates that sport broadcasting offers genuine opportunities to maintain linguistic and cultural diversity in small nations, even in a context characterized by escalating competition, dwindling resources, and the proliferation of multiple viewing portals.